PERMAINAN EDUKATIF (MISSING LYRICS) DALAM MENINGKATKAN KETERAMPILAN MENDENGAR SANTRI DI MARKAZ ARABIYAH PONDOK PESANTREN AL-QODIRI 1 JEMBER - Priyono, Dwi Juli; Azisi; Elok Rufaiqoh (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Arabic language learning cannot be separated from efforts to improve the four language skills. There are many ways to enhance students' listening skills, one of which is by using enjoyable educational games. In Arabic language learning, appropriate methods are also required to effectively implement educational games such as